A Multi-Dimensional Approach to the Sustainable Development of Moa Buffaloes in Maluku Province, Indonesia - Jomima Martha Tatipikalawan; Fransiskus Trisakti Haryadi; Endang Sulastri; Tri Satya Mastuti Widi (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
The purpose of the study was to determine the level of sensitivity of the indicator for the sustainability of the Moa Buffalo development based on the results of the identification and measurement of the index with a multidimensional approach on ecological, socio-cultural, and economic dimensions. The unit of analysis in this study, which was conducted on Moa Island, Maluku Province, was 261 farmer households and 16 experts who were selected using purposive sampling technique. Data collection method: literature study, Focus Group Discussion, in-depth interview, survey, measurement. The research variable is the development potential of the Moa Buffalo from 3 dimensions of sustainable Moa Buffalo development (ecology, socio-culture, economy), including 40 indicators. Data analysis using ordination technique Rap-BANGKER through the Multi-Dimensional Scaling (MDS) method to measure the index and status of sustainability and Leverage Analysis, to determine the key factors, Monte Carlo Analysis to assess the effect of errors on the estimated value of ordination for the development of the Moa Buffalo. The results showed that the average value of the Moa buffalo development index was 52.72% (sustainable). The ecological dimension is 41.15% (less sustainable) with 7 sensitive indicators, socio-cultural dimension is 60.28% (sustainable) with 5 sensitive indicators, economic dimension is 56.73% (sustainable) with 3 sensitive indicators. The Monte Carlo analysis of the three dimensions shows the value of the sustainability index at the confidence level of 95%, the difference in value is <1, the coefficient of determination (R2) for the third dimension is 95.00%. The MDS Rap-BANGKER analysis model is adequate to estimate the sustainability of the development of Moa Buffalo, has a high level of confidence, can be used as an evaluation tool to rapid appraisal sustainability analysis of buffalo development in an area.